Exercise versus no exercise for the occurrence, severity, and duration of acute respiratory infections. - Grande, A. J.; Keogh, J.; Silva, V.; Scott, A. M. (Cochrane Database of Systematic Reviews, 2020)
Background: Acute respiratory infections (ARIs) last for less than 30 days and are the most common acute diseases affecting people. Exercise has been shown to improve health generally, but it is uncertain whether exercise may be effective in reducing the occurrence, severity, and duration of ARIs. This is an update of our review published in 2015.